MANAJAMEN PEMBANGUNAN EKONOMI BERBASIS ISLAM - Keysia Febrianti; Dewi Sartika; Amalia Ramadhani; Miftahul Jannah Jannah; Irham Basri (ICONS: Islamic Economics Journal, 2025)
The problem of Islamic economic development is still an interesting topic to discuss. The need for an Islamic-based economic development strategy as an effective solution to use. The purpose of writing this research is to find out about the strategy of Islamic economic development. This type of research is a literature review research. This type of research collects data that is appropriate and relevant to the problem topic from several literatures. The data used comes from previous studies, journal articles, books, and other documents containing theories and information that are in accordance with the topics needed. The results of the study show that there are several strategies recommended by Islam to be implemented in the economic development of a country, namely: Good management of natural resources, improving the quality of human resources, utilization of technology, innovation in the development of MSMEs, and the role of government. If the above strategies can be implemented properly, economic development will experience a positive increase.